Predictive factors of Hyperemesis Gravidarum: A systematic review. (July 2019) - Ioannidou, Pinelopi; Papanikolaou, Dimitrios; Mikos, Themistoklis; Mastorakos, George; Goulis, Dimitrios G.
Abstract: Purpose: Hyperemesis gravidarum (HG) is the main cause of hospitalization during the first trimester of pregnancy. Although it has been associated with serious complications, little is known about its predictive factors. The aim of this systematic review was to search for and critically appraise the studies that investigate the predictive factors for HG. Methods: Search strategy included PubMed, CENTRAL and EMBASE databases (till December 2017). All studies examining risk factors for HG were included. Screening of available studies was carried out by two reviewers, as well as the quality assessment of the included studies, based on the Newcastle-Ottawa Scale for observational studies. Results: The search located 308 articles, of which 14 observational studies (four low-, eight medium- and two high-quality), involving 1400 women who met the eligibility criteria. In four studies, there was no association between Helicobacter (H.) Pylori infection and HG, in contrast to two studies which demonstrated such an association. Pre-pregnancy body mass index (BMI), adipose tissue, maternal age, leptin, ghrelin, beta-chorionic gonadotropin (β-hCG), total (T4 ) and free thyroxine (fT4 ) correlated with HG in various studies, and could be considered as predictive markers. Regarding the high-quality evidence, a cohort study associated leptin and nephatin-1 with HG, whereas a cross-sectional study found no association between H. pylori infection and HG. Conclusions: More studies of high quality and adequate sample size have to be carried out to identify the predictive factors for HG.